The Design of New HIV-IN Tethered Bifunctional Inhibitors Using Multiple Microdomain Targeted Docking - Ciubotaru, Mihai; Musat, Mihaela G.; Surleac, Marius; Ionita, Elena; Petrescu, Andrei Jose; Abele, Edgars; Abele, Ramona (Current Medicinal Chemistry, 2019)
Currently, used antiretroviral HIV therapy drugs exclusively target critical groups in the enzymes essential for the viral life cycle. Increased mutagenesis of their genes changes these viral enzymes, which once mutated can evade therapeutic targeting, effects which confer drug resistance. To circumvent this, our review addresses a strategy to design and derive HIV-Integrase (HIV-IN) inhibitors which simultaneously target two IN functional domains, rendering it inactive even if the enzyme accumulates many mutations. First we review the enzymatic role of IN to insert the copied viral DNA into a chromosome of the host T lymphocyte, highlighting its main functional and structural features to be subjected to inhibitory action. From a functional and structural perspective we present all classes of HIV-IN inhibitors with their most representative candidates. For each chosen compound we also explain its mechanism of IN inhibition. We use the recently resolved cryo EM IN tetramer intasome DNA complex onto which we dock various reference IN inhibitory chemical scaffolds such as to target adjacent functional IN domains. Pairing compounds with complementary activity, which dock in the vicinity of a IN structural microdomain, we design bifunctional new drugs which may not only be more resilient to IN mutations but also may be more potent inhibitors than their original counterparts. In the end of our review we propose synthesis pathways to link such paired compounds with enhanced synergistic IN inhibitory effects.
Keywords: RT